Recommendations for promoting patient safety and quality of care in the prison system: an integrative review (Revista Contexto & Saúde, 2026)
Health incidents occurring in the prison system are not uncommon, and patient safety remains under-theorized in extra-hospital settings. The objective of this study was to identify, in the literature, recommendations for promoting patient safety and quality of care in the prison system. An integrative review was conducted in January 2024 using the BDENF, IBECS, LILACS, MEDLINE, and SciELO databases, including publications up to the year 2023. Of the 185 articles initially identified, 20 were included in the analysis. Nineteen recommendations were synthesized to promote safety and quality of health care in the prison context, highlighting access for persons deprived of liberty to health services, multidisciplinary team, and early diagnosis of diseases and health conditions; control and supervision of the medication management process; professional training and education; adequate health workforce staffing; development of guidelines and policies; and risk management. The identified actions, when applied in practice, may contribute to the quantitative and qualitative advances necessary to provide value-based care to persons deprived of liberty and to meet the principles of the Sustainable Development Goals.
Keywords: Patient Safety; Prisons; Quality Indicators in Health Care; Nursing